Syrian hamster dermal cell immortalization is not enhanced by power line frequency electromagnetic field exposure - Gamble, S C (Nature Publishing Group, 1999)
Several epidemiological studies have suggested associations between exposure to residential power line frequency electromagnetic fields and childhood leukaemia, and between occupational exposure and adult leukaemia. A variety of in vitro studies have provided limited supporting evidence for the role of such exposures in cancer induction in the form of acknowledged cellular end points, such as enhanced mutation rate and cell proliferation, though the former is seen only with extremely high flux density exposure or with co-exposure to ionizing radiation. However, in vitro experiments on a scale large enough to detect rare cancer-initiating events, such as primary cell immortalization following residential level exposures, have not thus far been reported. In this study, large cultures of primary Syrian hamster dermal cells were continuously exposed to power line frequency electromagnetic fields of 10 100 and 1000 μT for 60 h, with and without prior exposure to a threshold (1.5 Gy), or sub-threshold (0.5 Gy), immortalizing dose of ionizing radiation. Electromagnetic field exposure alone did not immortalize these cells at a detectable frequency (≥ 1 × 10(−7)); furthermore, such exposure did not enhance the frequency of ionizing radiation-induced immortalization. © 1999 Cancer Research Campaign